Regressive Structures for Computation of DST-II and Its Inverse. (21st November 2012) - Jain, Priyanka; Jain, Anamika
Abstract : Efficient regressive structures for implementation of forward (DST-II) and inverse discrete sine transform (IDST-II) are developed. The proposed algorithm not only minimizes the arithmetic complexity compared to the existing algorithms (Wany (1990), Hupta and Rao (1990), Yip and Rao (1987), Murthy and Swamy (1992)) but also provides hardware savings over the algorithm (Jain et al. (2008)) by the same authors. The naturally ordered input sequence makes the new algorithms suitable for on-line computation.